Reversal of Development in Argentina : Postwar Counterrevolutionary Policies and Their Structural Consequences - Waisman, Carlos Horacio (Book collections on Project MUSE., 2014)
Carlos Waisman has pinpointed the specific beliefs that led the Peronists unwittingly to transform their country from a relatively prosperous land of recent settlement, like Australia and Canada, to an impoverished and underdeveloped society resembling the rest of Latin America. Originally published in 1987. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These paperback editions preserve the original texts of these important books w.